Il Secolo Illustrato, Progetto D'un Viaggio Al Polo Nord in Pallone - Unknown (Massachusetts Institute of Technology. Libraries. Department of Distinctive Collections, 1890)
Clipping from the Italian newspaper "Il Secolo Illustrato" containing illustrations of S.A. Andreé's balloon for North Pole exploration. One image shows the balloon in the clouds dragging a guide rope, one shows the outside of the balloon carriage with a boat tied to its side and one shows a cross-section of the inside of the carriage. For more information about this item, visit https://archivesspace.mit.edu/repositories/2/digital_objects/815